Central African Economic and Monetary Community : Common Policies in Support of Member Countries Reform Programs-Staff Report; and Statement by the Executive Director. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2021)
Context and risks. The pandemic may have a long-lasting impact on CEMAC's growth potential, which is already curtailed by structural, governance, and transparency issues. The policy response from national and regional authorities in 2020 helped mitigate the economic fallout. CEMAC, however, experienced a severe recession in 2020, fiscal and external deficits increased, and public debt rose with some countries having debt sustainability issues. The region is facing an increasing dilemma between internal and external stability, as external reserves fell sharply between mid-2020 and March 2021. A moderate recovery in economic growth is expected from 2021. Supported by lower than previously projected total external financing of Euro 4.8 billion over 2021-23, international reserves build-up would be slower than pre-pandemic. This outlook is highly uncertain and contingent on the evolution of the pandemic and the vaccination program. Other significant risks include delayed implementation of the ongoing or possible new Fund-supported programs, uncertainties in filling large external financing needs, oil prices, and a possible deterioration in the security situation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance